2019
DOI: 10.1111/echo.14308
|View full text |Cite
|
Sign up to set email alerts
|

The echocardiographic assessment of the right ventricle in patients with arrhythmogenic right ventricular cardiomyopathy/dysplasia compared with athletes and matched controls

Abstract: Background There are discrepancies in the quantitative echocardiographic criteria for the right ventricle (RV) between the revised task force criteria (TFC) for Arrhythmogenic Right Ventricular Cardiomyopathy/Dysplasia (ARVC/D) and the guidelines for RV assessment endorsed by American Society of Echocardiography (ASE). Importantly, these criteria do not take into account potential adaptation of the RV to exercise. The goal of this study was to compare the revised TFC quantitative echocardiographic parameters i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The echocardiogram is a beneficial, non-invasive diagnostic test to assess structural changes in ARVC [ 38 - 40 ]. Echocardiogram changes meeting major diagnostic criteria present in 39% of our patients.…”
Section: Discussionmentioning
confidence: 99%
“…The echocardiogram is a beneficial, non-invasive diagnostic test to assess structural changes in ARVC [ 38 - 40 ]. Echocardiogram changes meeting major diagnostic criteria present in 39% of our patients.…”
Section: Discussionmentioning
confidence: 99%
“…There is a significant overlap between myocardial RV morphologic alterations described in ARVC and the athlete’s heart [ 5 , 6 , 7 ]. The revised 2010 TFC were developed in order to improve the diagnosis of ARVC.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, observational echocardiographic studies reported contrasting findings for cardiac function and dimensions in athletes compared to ARVC [ 5 , 6 , 7 ]. Data about the physiological exercise-induced alterations involving the right atrium (RA) in athletes compared to patients with ARVC is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Other CMR studies reported a prevalence of ACM mimics between 4.4% and 5% 21,22 . In a small study that included 51 patients (20 with ACM, 11 athletes and 20 controls), echocardiographic criteria as established by both TFC and ASE, were not able to differentiate between ACM patients and athletes 23 . Another study that compared 34 healthy athletes with 34 ACM patients and 8 trained athletes with ACM using CMR, aimed to assess the diagnostic effi ciency of RV end-diastolic volume (RVEDV) and RV EF and the additional value of strain analysis.…”
mentioning
confidence: 94%